Changes in liver-related mortality by etiology and sequelae: underlying versus multiple causes of death - Ming-Jen Sheu; Fu-Wen Liang; Ching-Yih Lin; Tsung-Hsueh Lu (BMC, 2021)
Abstract Background The expanded definition of liver-related deaths includes a wide range of etiologies and sequelae. We compared the changes in liver-related mortality by etiology and sequelae for different age groups between 2008 and 2018 in the USA using both underlying and multiple cause of death (UCOD and MCOD) data. Methods We extracted mortality data from the CDC WONDER. Both the absolute (rate difference) and relative (rate ratio and 95% confidence intervals) changes were calculated to quantify the magnitude of change using the expanded definition of liver-related mortality. Result Using the expanded definition including secondary liver cancer and according to UCOD data, we identified 68,037 liver-related deaths among people aged 20 years and above in 2008 (29 per 100,000) and this increased to 90,635 in 2018 (33 per 100,000), a 13% increase from 2008 to 2018. However, according to MCOD data, the number of deaths was 113,219 (48 per 100,000) in 2008 and increased to 161,312 (58 per 100,000) in 2018, indicating a 20% increase. The increase according to MCOD was mainly due to increase in alcoholic liver disease and secondary liver cancer (liver metastasis) for each age group and hepatitis C virus (HCV) and primary liver cancer among decedents aged 65-74 years. Conclusion The direction of mortality change (increasing or decreasing) was similar in UCOD and MCOD data in most etiologies and sequelae, except secondary liver cancer. However, the extent of change differed between UCOD and MCOD data.